Inverted Meckel’s diverticulum: a rare cause of intussusception in children - Nayak, Sitikantha; Mishra, Baikuntha Narayan; Patra, Sudhansu Sekhar; Joshi, Ranjit Kumar; Pahi, Prabin Prakash; Paikray, Rajlaxmi (International Journal of Research in Medical Sciences, 2020)
Invagination of proximal segment of intestine to distal one results in intussusceptions and is a common cause of intestinal obstruction in children. In most of the cases of intussusceptions, the cause is idiopathic in nature; the other causes may be infection, polyp or anatomical abnormalities. Occasionally, Meckel’s diverticulum may cause intussusception and inverted Meckel’s diverticulum leading to intussusceptions is very rare in children. It is difficult to diagnose inversion of Meckel’s diverticulum preoperatively. Here in we report a case of 6 yrs old male child, who was operated for intussusception and found to have inverted Meckel’s diverticulum as lead point.